Reliability, usefulness, and factorial validity of change-of-direction speed tests in adolescent basketball players - Stojanovic, E.; Aksovic, N.; Stojiljkovic, N.; Stankovic, R.; Scanlan, A.; Milanovic, Z. (The Journal of Strength and Conditioning Research, 2019)
The purposes of this study were to (1) determine the reliability, usefulness, and factorial validity of change-of-direction speed (CODS) tests in adolescent basketball players and (2) evaluate positional differences in test performances. Elite, adolescent male basketball players (n = 53; 17.3 ± 1.0 years) completed 6 CODS tests: "Lane Arrow Closeout," "Lane Agility Drill," "Reactive Shuttle Test," "Run-Shuffle-Run," "Compass Drill," and "Modified 505 Test." Players completed 3 trials of each test. All tests demonstrated acceptable reliability (intraclass correlation coefficient: 0.50-0.88; coefficient of variation: 5.1-7.9%). The typical error (TE) calculated for each test was above the smallest worthwhile change, rating the usefulness of all tests as marginal. The principal component factor analysis in all tests resulted in the extraction of one significant component that explained 74% of the total variance across tests. Positional comparisons showed that backcourt (guards) players performed better (small to moderate differences) in all CODS tests compared with frontcourt (forwards and centers) players. All tests were deemed reliable and valid in adolescent basketball players. The "Lane Agility Drill" and "Run-Shuffle-Run" tests seem the most appropriate to quantify changes in CODS possessing the lowest TE, whereas the "Lane Arrow Closeout" and "Lane Agility Drill" tests are the most sensitive in detecting positional differences.